Metaphors of illness in news reports in a Malaysian newspaper - Priyadarshni, R. Lakshmi (2016)
In April 2009, reports of a new strain of a deadly flu virus emerged in Mexico. The scarcity of information available on this new threat can be observed clearly in the language used in the news reports. This study investigates the use of conceptual metaphors of the Influenza A (H1N1) pandemic in the newspaper and how these metaphors helped to construct the notion of a pandemic in the media. Metaphors of illness and disease are a prominent tool in the discourse of disease in the news. The conceptual metaphor theory by Lakoff and Johnson(1980) was utilized as a framework in this study to investigate the coverage of the pandemic in the newspaper. The data was extracted from a corpus of news reports from The New Straits Times Malaysia from April 2009 to August 31, 2009 when the disease was at its peak. The results of the study yielded various conceptualisation and construction of the pandemic at various stages in the news. Three dominant conceptual metaphors; DISEASE IS A WAR, DISEASE IS A CRIMINAL and DISEASE IS A POSSESSION and ten least dominant conceptual metaphors were found in the research. Metaphors of war; the most conventional construction were found to be prominent at the beginning of the outbreak. Furthermore, as the disease progressed in the country, shifts in the conceptualisation of the pandemic in the news as a CRIMINAL and a POSSESSION constructed a notion of pandemic from a foreign threat to a more internalized problem with the country and a shift in the culpability of controlling the disease.